The arts of Angela Carter : a cabinet of curiosities - Mulvey Roberts, Marie (Manchester University Press, 2019)
The arrangement of the material, indicated by the chapter headings, draws attention to a variety of areas not normally associated with dominant perceptions of Angela Carter. These encompass food, fashion, art, poetry, music, performance and translation, which will be discussed in a number of historical, literary and cultural contexts.